Epidemiological characteristics of rape against women in the state of Tocantins, 2009 to 2019 (Research, Society and Development, 2022)
Introduction: The violence against women is a major public health problem worldwide particularly in developing countries, including Brazil. Methodology: This is a descriptive study with data on sexual violence from the Department of Informatics of the Unified Health System (DATASUS). All cases of rape against women residing in the state of Tocantins from 2009 to 2019 were analyzed, totaling 3,753 cases. Results: The trend of rape records was increasing and went from 1.33% in 2009 to 16.01% in 2019. The victims were predominantly brown (76.76%), between 10 and 14 years old (45.46%), between 5th and 8th grade incomplete (36.16%), living in the Capim Dourado health areas (43.65%), the most common place of rape (69.25%) was the victim's residence, with the majority being repeat violence (45.86%) and committed by a family friend/acquaintance (26.38%). The main perpetrator was a friend/acquaintance (25.45%), followed by boyfriend (15.89%) and stepfather (12.09%). Of the rapes that occurred in schools, the main perpetrator was a friend/acquaintance (40%), as well as in commerce/services (40%). Discussion: Rape against women is a public health problem in Tocantins, the severity is even greater because this violence is more frequent in the home environment and repetition. Final Considerations: The results of this research can contribute to policies and interventions aimed at minimizing violence against women, as the increasing prevalence of records by health services must be treated as a significant social problem.